PENGARUH AFTER SALES SERVICE BERBASIS TEKNIS BUDIDAYA AYAM DAN PROGRAM LOYALTY REWARD TERHADAP KEPUASAN PELANGGAN DALAM MEMBENTUK LOYALITAS PELANGGAN (Studi Pada Pelanggan Pakan Ternak di Kalimantan) - Sofyan Haris; Muhammad Riza Firdaus; Ahmad Rifani (JWM (JURNAL WAWASAN MANAJEMEN), 2017)
The purpose of this research is to know the effect of afters-sales service based on chicken farming technique (X1) and loyalty reward program (X2) as independent variable to customer satisfaction (Y1) in shaping customer loyalty (Y2) animal feed in Kalimantan as dependent variable. The method used in this research is to collect the data with the questionnaire survey technical to the livestock feed customer in Kalimantan Island. Determination of the research sample using non-probability sampling method of purposive sampling type with the criteria has been purchasing feed for more than 3 years, have felt the benefits of the company and have farm broiler, laying hens, ducks. The measurement of variables using the bipolar adjective scale of perfection of the semantic scale with the two extreme categories "strongly disagree (1)" and "strongly agree (10)". Survey data for variables X1, X2, to Y1 and Y2 are then analyzed by Structural Equation Modeling method using AMOS. The results showed that after-sales service based on chicken farming technique (X1) had significant effect on customer satisfaction (Y1) animal feed. Loyalty reward program (X2) has a significant effect on customer satisfaction (Y1) and has significant effect on customer loyalty (Y2) of animal feed. Similarly, customer satisfaction (Y1) has a significant effect on customer loyalty (Y2) fodder in Kalimantan. The conclusion of this research is that loyalty reward program (X2) has the most dominant influence to increase customer loyalty (Y2), and loyalty reward program (X2) with after sales service based on chicken culture technique (X1) can influence customer satisfaction (Y1) to increase customer loyalty (Y2) fodder in Kalimantan. Suggestion from this research is animal feed company should apply loyalty reward program and after sales service to increase customer loyalty